STUDY OF ELECTRONIC JUNCTION OF N719 DYE/POLYANILINE ON THE PHOTOANODE IN A DYE-SENSITIZED SOLAR CELLS - Ramadhan Putra, Rizki
Solar cell sensitized by dye or so-called Dye-Sensitized Solar Cells (DSSC) is a new breakthrough solar cell that utilizes dye excited electron to flow through an external circuit then return back to dye to produce an electric current. Here, ruthenium metal complex, dye N719, was used as a sensitizer. The regeneration of the electrons from the electrolyte redox system into dye requires a longer time than other processes in the electron flow. Here, Polyaniline (PANI) was deposited on photoanode with screen-print method as hole transport material between electrolyte and dye. Absorbance of PANI coated photoanode was measured using a UV-Vis spectrophotometer and the fabrication result as a complete cell was measured using the solar simulator Oriel S013A and V-I Keithley 2400. Photoanode which has been coated by PANI has a higher absorbance than without PANI and the fabricated cell generated better maximum work (Fill Factor) than the standard due to the presence of PANI which helps regenerate the electrons in the dye. However, the generated Jsc were smaller due to recombination between dye and PANI that may occur and divide the flow of electron. The produced Voc were also smaller because the energy level of the ground state of PANI is higher than the electrolyte system. The decreased of Jsc and Voc leads to a lower efficiency. The thermal annealing process may improve the efficiency of the cell which reach the optimum temperature at 40 oC.